Native and fermented waxy cassava starch as a novel gluten-free and clean label ingredient for baking and expanded product development - Dufour, Dominique; Rolland Sabaté, Agnès; Cordoba, Hansel A. Mina; Melendez, Jorge Luis Luna; Moreno Alzate, Jhon Larry; Pizzaro, Mónica; Guilois Dubois, Sophie; Sánchez, Teresa; Belalcázar, John Eiver; Morante, Nelson; Tran, Thierry; Moreno Santander, Martin A.; et al. (Royal Society of Chemistry, 2022)
Amylose-free and wild-type cassava starches were fermented for up to 30 days and oven- or sun-dried. The specific volume (ν) after baking was measured in native and fermented starches. The average ν (across treatments) for waxy starch was 3.5 times higher than that in wild-type starches (17.6 vs. 4.8 cm3 g−1). The best wild-type starch (obtained after fermentation and sun-drying) had considerably poorer breadmaking potential than native waxy cassava (8.4 vs. 16.4 cm3 g−1, respectively). The best results were generally obtained through the synergistic combination of fermentation (for about 10–14 days) and sundrying. Fermentation reduced viscosities and the weight average molar mass led to denser macromolecules and increased branching degree, which are linked to a high loaf volume. The absence of amylose, however, was shown to be a main determinant as well. Native waxy starch (neutral in taste, gluten-free, and considerably less expensive than the current alternatives to cassava) could become a new ingredient for the formulation of clean label-baked or fried expanded products.